2016
DOI: 10.1007/s10266-015-0223-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia enhances the effect of lipopolysaccharide-stimulated IL-1β expression in human periodontal ligament cells

Abstract: Oral infection is inflammatory disease caused by bacteria. A major component of gram negative bacteria membrane associated with inflammation is lipopolysaccharide (LPS). Currently, evidence presenting the combined effect of LPS and hypoxia to inflammatory response in human periodontal ligament cells (HPDLs) was yet lacking. Here, we studied whether the influence of oxygen on LPS-stimulated inflammatory cytokines in HPDLs. HPDLs were stimulated with LPS in normoxia and hypoxia for 24 h. The mRNA and protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…However, these data are not comparable to the LPS dose used in in‐vitro studies as the LPS contained in the serum is pretty low and that measured in gingival crevicular fluid is presented with the activity of the endotoxin. Thus, we referred to the corresponding in‐vitro research and chose the most commonly used quantities of P. gingivalis LPS for our experiment planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these data are not comparable to the LPS dose used in in‐vitro studies as the LPS contained in the serum is pretty low and that measured in gingival crevicular fluid is presented with the activity of the endotoxin. Thus, we referred to the corresponding in‐vitro research and chose the most commonly used quantities of P. gingivalis LPS for our experiment planning.…”
Section: Discussionmentioning
confidence: 99%
“…To test the dose‐dependent effects, the PDLFs were cultured in the presence of P. gingivalis LPS at concentrations of 0.001, 0.01, 0.1, 1 and 10 μg/mL for 24 hours. The concentrations of P. gingivalis LPS (0.001‐10 μg/mL) we selected, which could be refined to different experiment protocols, are based on previous research regarding the in‐vitro PDLF cultures . To investigate the time‐dependent effects, P. gingivalis LPS of the optimal concentration (0.1 μg/mL) was used to stimulate the PDLFs for different experimental periods (6, 12, 24 and 48 hours).…”
Section: Methodsmentioning
confidence: 99%
“…IL-1 beta is produced by activated macrophage and stimulates the maturation and proliferation of B cells and the release of more inflammatory mediators, which results in inflammation and tissue damage [ 25 ]. Also, high-altitude and hypoxia conditions could enhance IL-1 beta secretion [ 22 , 25 , 26 ]. IL-2, which is known as a T cell survival factor, plays a key role in immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that a hypoxic environment may upregulate proinlammatory cytokines and MMPs' expression from host cells during periodontal disease [34]. The idea was that hypoxia further encourages lipopolysaccharide (LPS)-induced TNF-α, interleukin-1β, and interleukin 6 (IL-6) expressions via LPS toll-like receptor (TLR) interaction that, in turn, activates the nuclear factor kappa B (NF-κB) pathway in human PDL cells upon exposure to the aforementioned Gram-negative bacterial surface component [35][36][37].…”
Section: Hypoxia and Chronic Periodontal Inlammationmentioning
confidence: 99%